The Effect of Nearpod Toward Tenth-Grade Students’ Reading Skill in A Public Senior High School in North Bali, Indonesia - Wanda Dian Paramesti Fortuna Dewi; Made Hery Santosa; Kadek Sintya Dewi (Institut Agama Islam Negeri Madura, 2023)
ABSTRACT This research aims to find out the effect of ICT tool, Nearpod, on students' reading skill. The researcher employed a mixed-method approach by combining a post-test-only design and an interview guide. An independent-sample t-test is carried out to examine quantitative data, whereas interactive model analysis is used to analyze qualitative data. The research population including tenth-grade students at SMA Negeri 1 Banjar. 29 students from X8 class are set as experimental group and 31 students from X1 as control group. The research findings revealed that the implementation of Nearpod significantly affects students’ reading skill at SMA Negeri 1 Banjar. The result show mean score of experimental group (M=80.76) is higher compared to control group (M=70.77). The interview results revealed that Nearpod positively impacted the reading-learning process. Students can access the material anytime and from any location via Nearpod. Additionally, it improves learning effectiveness, efficiency, and interest. Further study is encouraged to investigate the effect of Nearpod on other English skills, disciplines, or levels. Keywords: Reading Skill, Nearpod, English Language, MALL, ICT Tools in ELT . ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh perangkat TIK, Nearpod, terhadap keterampilam membaca siswa. Peneliti menggunakan pendekatan campuran dengan mengabungkan desain post-test only dan wawancara. Independent-sample t-test digunakan untuk menguji data kualitatif, sementara model analisis interaktif digunakan untuk menganalisis data kualitatif. Populasi penelitian meliputi siswa kelas 10 di SMA Negeri 1 Banjar. 29 siswa yang berasal dari kelas X8 ditetapkan sebagai kelompok eksperimen dan 31 siswa dari kelas X1 ditetapkan sebagi kelompok kontrol. Hasil penelitian mengungkapkan bahwa pengimplementasian dari aplikasi Nearpod secara signifikan telah mempengaruhi keterampilan membaca siswa di SMA Negeri 1 Banjar. Hasil menunjukan rata-rata dari grup eksperimental (M=80.76) lebih tinggi dibandingkan dengan rata-rata grup kontrol (M=70.76). Hasil interview menunjukan bahwa Nearpod secara positif telah mempengaruhi proses pembelajaran membaca suswa. Siswa dapat dengan mudah mengakses materi kapanpun dan dimanapun dengan Nearpod. Nearpod juga meningkatkan efektivitas, efesiensi, dan ketertarikan dalam belajar. Penelitian lebih lanjut dianjurkan untuk meneliti pengaruh Nearpod pada keterampilan Bahasa Inggris, disiplin ilmu, atau pada level yang berbeda. Kata Kunci: Keterampilan Membaca, Nearpod, Bahasa Inggris, MALL, Perangkat TIK dalam Pembelajaran Bahasa Inggris